Local increase in trapezius muscle oxygenation during and after acupuncture - Ohkubo, M.; Hamaoka, T.; Niwayama, M.; Murase, N.; Osada, T.; Kime, R.; Kurosawa, Y.; Sakamoto, A.; Katsumura, T. (Dynamic Medicine, 2009)
This study aimed to compare the trapezius muscle blood volume and oxygenation in the stimulation region and in a distant region in the same muscle during acupuncture stimulation (AS). We hypothesized that AS provokes a localized increase in muscle blood volume and oxygenation in the stimulation region. Two sets of near-infrared spectrometer (NIRS) probes, with 40-mm light-source detector spacing, were placed on the right trapezius muscle, with a 50-mm distance between the probes. Changes in muscle oxygenation (oxy-Hb) and blood volume (t-Hb) in stimulation and distant regions (50 mm away from the stimulation point) were measured using NIRS in 9 and 10 healthy acupuncture-experienced subjects for the experiment as the AS group and as the control group (no AS), respectively. Measurements began with a 3-min rest period, followed by "Jakutaku" (AS) for 2 min, and recovery after stimulation. There was a significant increase in oxy-Hb (60.7 muM at maximum) and t-Hb (48.1 muM at maximum) in the stimulation region as compared to the distant region. In the stimulation region, a significant increase in oxy-Hb and t-Hb compared with the pre-stimulation level was first noted at 58.5 s and 13.5 s, respectively, after the onset of stimulation. In conclusion, oxygenation and blood volume increased, indicating elevated blood flow to the small vessels, not in the distant region used in this study, but in the stimulation region of the trapezius muscle during and after a 2-min AS.